“Evaluación del control interno y su incidencia en la toma de decisiones en la empresa Agro Aéreo s.a. del cantón Quevedo, Provincia de los Ríos año 2020” - Chugchilan Baraja, Ángela Benita (2021)
The current research is to analyze the internal control and its impact on decision making in the company Agro Aéreo S.A., Quevedo Canton, Los Ríos Province year 2020, achieving the improvement of the company and the achievement of the objectives of the same. The research is applied and descriptive, which allowed applying improvement strategies, solving problems that exist within the company and analyzing and interpreting data obtained, observing the development of activities and situations at present to promote a possible solution, thus achieving the objectives or goals of the research. Relevant information on the company's problems was collected through techniques such as the internal control questionnaire. By means of the 5 components of COSO I, such as control environment, risk assessment, control activity, information and communication, supervision, and monitoring, a total score of 72% confidence level and a risk level of 28% was obtained. It was identified that the level of confidence in decision-making is medium with 60%. By proposing procedures, the internal control of each of the activities carried out by the departments can be improved, since this way they have defined their activities and functions, helping to achieve the desired goals. It was determined by means of the chi-square that the internal control has an impact on the decision-making of the company Agro Aéreo S.A. Finally, we proceeded to the elaboration of the proposal of a manual of functions and procedures in the company that will allow maintaining the updated records of the operations that are executed in the different areas that the entity has such as management, accounting, human talent, and production, in addition, the conclusions and recommendations that have been reached in the investigation are determined.